Evaluation of antioxidant activity of Ruta graveolens L. extract on inhibition of lipid peroxidation and DPPH radicals and the effects of some external factors on plant extract's potency. - S. Mohammadi- Motamed; S. Shahidi-Motlagh; H. Bagherzadeh; S. Azad Forouz; H. Tafazoli (Iranian Society of Pharmacognosy, 2014)
The antioxidant properties of Ruta graveolens L. were evaluated by two different methods; free radical scavenging using DPPH and inhibition of lipid peroxidation by the ferric thiocyanate method. The IC50 value of the methanol extract in DPPH inhibition was 200.5 μg/mL which was acceptable in comparison with BHT (41.8 μg/mL). In thiocyanate method, the plant extract demonstrated activity as much as BHT in prevention of lipid peroxidation. Increasing the temperature during extraction, significantly decreased the extract power in inhibition of DPPH radicals. The storage time and temperature had no effect on lipid peroxidation inhibition.